2022
DOI: 10.1186/s43591-022-00043-1
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in Namibian river sediments – a first evaluation

Abstract: The African continent is rarely the focus of microplastics research, although the ubiquity of microplastics in the environment is undisputed and still increasing. Due to the high production and use of plastic products and the partial lack of recycling systems in many parts of the African continent, it can be assumed that microplastic particles are already present in limnic and terrestrial ecosystems. Few studies, mainly from South Africa and the Northern African region, show a contamination with microplastics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 81 publications
(143 reference statements)
1
0
0
Order By: Relevance
“…The most dominant size range of MPs found in the Cagayan de Oro River, Philippines was 0.3–0.5 mm. This is comparable to the study conducted by Faulstich et al [ 105 ] in the sediments of the Namibian River, Namibia where this size range comprised 33.7% of the total MPs. In addition, the study conducted in the Tamsui River also identified 0.3–5 mm size range particles [ 106 ].…”
Section: Discussionsupporting
confidence: 89%
“…The most dominant size range of MPs found in the Cagayan de Oro River, Philippines was 0.3–0.5 mm. This is comparable to the study conducted by Faulstich et al [ 105 ] in the sediments of the Namibian River, Namibia where this size range comprised 33.7% of the total MPs. In addition, the study conducted in the Tamsui River also identified 0.3–5 mm size range particles [ 106 ].…”
Section: Discussionsupporting
confidence: 89%